A Critical Analysis of Naw'i Khabushāni's Divān - M.Mostafa Resalatpanahi; Hossien Ghorbanpour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Mohammad RezāKhabushāni, also known as Naw'i Khabushāni (970- 1019 AH), a famous poet in tenth century and the beginning of the eleventh century, was one of the indisputable masters of Persian literature in Indian peninsula.The poetry of his poems was published in 1374 by Amir-Hossein Zākerzādeh and the efforts of Ahmad Karami by Mā publication in Tehran. In this print, there are many shortcomings, distortions, weaknesses, and mistakes that often result from possible defects in handwriting or bad readiness and timeliness. These same factors have reduced the accuracy of this print and the poetry’s Naw'i that go away from the accuracy and eloquence.With the help of the older and more authoritative handwritten copies of the Divān, some of the mistakes in the poet’s poem can be corrected and revised.This research is a critical analysis and survey and checking of some of his poems, in which the writers criticized the abundance of his verses by holding two handwritten copies of the court of this poet and comparing it with the text of the Divan And have concluded that the current edition of the Divān has been taken without the use of scientific methods of correction and in no way worthy and deserving of this poet is not capable.